New Stretchers - School Mathematics Project (New York : Cambridge University press, 1991)
Consists of 32 double-sided cards containing a number of problems and activities to complement the work of abler pupils in Y7 and Y8. No initial input is required from the teacher and hints cards are included for pupils' use. Many problems could be tackled by pupils working in pairs or threes.
Keywords: Mathematics